Penggunaan Bumbu Andaliman Sebagai Bahan Utama Dalam Pengolahan Makanan (Studi Kasus Pembuatan Pizza Andaliman) Di Restoran Pizza Andaliman Balige Kabupaten Toba - Narwastu Murni; Lyandru Togu Mulia Tambunan (Tourism, Hospitality And Culture Insights Journal, 2022)
Andaliman pizza has a special taste. Andaliman pizza is processed by gently grinding andaliman, then sliced lemongrass, carrot parts, cabbage flowers, far beans and spring onions. After that the sausage part, soft slices of cheese and the tomato part become a garnish or accessory on the top of the pizza. This study has a purpose, namely to identify customer assumptions about the characteristics of pizza andaliman, to analyze customer attitudes to pizza andaliman, and to analyze customer actions to pizza andaliman. The data analysis procedure used in this study is to use SWOT analysis. There is also a final result from this study if Andaliman Pizza is one of the powerhouses for foreign tourists who are curious about its taste and texture